2014
DOI: 10.1097/md.0000000000000035
|View full text |Cite|
|
Sign up to set email alerts
|

Nationwide Longitudinal Analysis of Acute Liver Failure in Taiwan

Abstract: Acute liver failure (ALF) is uncommon but fatal. Current management is based mostly on clinical experience. We aimed to investigate the incidence, etiology, outcomes, and prognostic factors of ALF in Taiwan. Patients with the admission diagnosis of ALF between January 2005 and September 2007 were identified from the Longitudinal Health Insurance Database of Taiwan. ALF was further confirmed by disease severity based on laboratory orders, prescriptions, and duration of hospital stay, and acute onset without pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
2
18
1
Order By: Relevance
“…There is high prevalence of acetaminophen associated ALF in the United Kingdom and in the United States. The most common etiologies in Taiwan(Ho et al, 2014) were viral (45.4%, mainly Hepatitis B virus) and These factors are different from this study. Because of variations in the etiology of ALF in different geographic regions, the prognostic factors may also be different.…”
contrasting
confidence: 82%
“…There is high prevalence of acetaminophen associated ALF in the United Kingdom and in the United States. The most common etiologies in Taiwan(Ho et al, 2014) were viral (45.4%, mainly Hepatitis B virus) and These factors are different from this study. Because of variations in the etiology of ALF in different geographic regions, the prognostic factors may also be different.…”
contrasting
confidence: 82%
“…However, an APAP overdose causes severe liver damage that has the potential to progress to liver failure, which accounts for nearly half of the liver failure cases in the USA and a significant portion of cases in Europe [ 2 ]. In Taiwan, an APAP overdose is also an important cause of acute liver failure [ 3 ]. An APAP toxic metabolite, N -acetyl- p -benzoquinone imine (NAPQI), is believed to be responsible for APAP-induced hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, sepsis is one of the poor prognostic factors for ALF [ 1 ]. Fujiwara et al [ 10 ] reported that bacterial bloodstream infection was found in 35% of cases with infectious complications in autoimmune ALF [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liver transplantation is an essential treatment option for ALF. Ho et al [ 1 ] have reported that infectious diseases, alcohol abuse, and malignancy are several risk factors associated with poor prognosis in ALF patients. Clinicians need to pay special attention to the management of these risk factors.…”
Section: Introductionmentioning
confidence: 99%